Child marriages and the right to education: the legal and social perspective - Maheran, Makhtar; Nor Aida, Ab. Kadir (2018)
Recently, Malaysians were alarmed with the shocking news of a marriage between 11 year-old Thai girl and a 41 year-old Kelantanese man that took place in Thailand. Though the marriage was valid as it fulfilled all the requirements under Islamic Law, it could not be registered in Malaysia without the consent of a Syariah Court as the bride was below the minimum age permitted by Malaysian Law. The man was prosecuted and received a penalty but the girl remains as a wife. Being a wife, she would shoulder a lot of responsibilities and must also be able to sacrifice a lot of things. It was reported that the man allowed the girl to continue religious schooling but it was declined by the latter. Without sufficient knowledge and experience, the girl’s future would solely depend on her husband and the parent. Thus, this research paper aims to study on the issue of child marriages in Malaysia and how it would affect children legally and physiologically. This paper also intends to examine on the right to education with special reference to married children. It is therefore suggested that special care should be placed on the married children, particularly on their right to education and their right to be able to hold the future at their own hands.